Membentuk Karakter Bangsa pada Masyarakat Multikultural Maluku Utara - Wahyudin Noe; Sitirahia Hi Umar (Universitas Khairun, 2020)
The phenomenon of the nation's problems until now has not been resolved from various conflict events that smelled of ethnicity, religion, and race (SARA) because of the strong attitude of intolerance and sectoral egoism. This issue is important to be raised, bearing in mind the living conditions of the people of North Maluku with a high level of cultural diversity (multicultural), both the diversity of languages, ethnicities, ethnicities, and religions as examples in good living. Although it looks diverse, the activities of daily community life look safe and peaceful. Of course, diversity is seen as a social reality for people to know each other, respect and respect each other, and build better brotherhood without looking at different social backgrounds. Such living conditions must be jointly guarded by all components of the nation including government, community leaders (religious leaders, ethnic leaders, youth leaders, academics), and parents. The need for a high anticipatory attitude to prevent from various potential social conflicts. Therefore, this anticipatory form is carried out by strengthening the role of the three education environment sectors, namely: (1) formal education (in schools and colleges); (2) non-formal education (in the community); and (3) informal education (in the family and environment) to shape national character values such as tolerance, democratic values, and cooperation values in multicultural societies. The formation of national character values informal education can be held through the process of character learning in all subjects and the habituation process in the association of students in schools/colleges. While the formation of the nation's character in non-formal education can be through community activities organized by the community and the government such as workshops (training), upgrading and socialization, where the community activities can provide the understanding and build community awareness to further recognize the importance of values national character value. While the formation of the nation's character in informal education can be through guidance and exemplary parenting and community leaders. The three paths of the educational environment, have an important role to shape the character of the nation so they can build a multicultural life that is peaceful, harmonious, and harmonious.